Unveiling the Emission Mechanisms of Blazar PKS 1510−089. II. Jet−BLR Connection and Black Hole Mass Estimation - Alfredo Amador-Portes; Vahram Chavushyan; Víctor M. Patiño-Álvarez; José Ramón-Valdés (The Astrophysical Journal)
The flat spectrum radio quasar PKS 1510−089 is one of the most active blazars across the entire electromagnetic spectrum, displaying periods of flaring activity. This study explores its spectral variability over a decade. By employing the nonthermal dominance parameter, we analyze the H β and λ 5100 continuum light curves, as well as the FWHM of the H β emission line, to identify whether the primary source of the continuum emission is the accretion disk or the jet during activity periods. Our results show an anticorrelation between the FWHM and the luminosity of the H β emission line across all data sets. This indicates that variations in H β luminosity consistently reflect the canonical broad-line region (BLR), irrespective of whether the primary ionizing source is the accretion disk or the jet. The anticorrelation persisted when comparing the FWHM of H β against the luminosity at λ 5100 in the disk dominance regime. These findings, along with the observation that flaring events in the λ 5100 continuum, attributed to the jet, coincide with flares in the H β emission line, suggest that the base of the jet is located within the BLR. Based on the 219 spectra within the disk dominance regime, we estimated a mean black hole mass of M _BH  = 2.85 ± 0.37 × 10 ^8 M _⊙ .